CONSEQUENCES OF NEOCONSTITUTIONALISM: THE JUDICIARY AS A SUPEREGO OF SOCIETY - Silva Mota, Deborah (2021)
After World War II, there were major changes in the constitutional scenario, emerging the neoconstitutionalism. With the new model, the constitutions started to join the American standard based on the Supremacy of the Constitution and the obligation of the legislators to make it effective (the constitution). As such, the Judicial Power began to handle certain issues that had not been brought before to it, giving greater power to the Jurisdictional Function by adopting the mechanism of Constitutionality Control. The assign of the present theme was due to the fact that there are numerous decisions of the Federal Supreme Court that do not live up to the function of Guardian of the Constitution, yet acting as legislator, denoting a judicial activism not fixed in its competences. This is how the Judiciary becomes the contemporary monarch, in which the population lodge their problems and await years for a solution.   Keywords: Neo-constitutionalism. Judicial Activism. Federal Court of Justice. Constitution.